A study of aspiration cytology of various thyroid lesions and histopathological correlation - Venu Anand; Selvi S.; Pushpa B (International Journal of Medical Research and Review, 2017)
Background: Thyroid swelling is one of most common neck swelling encountered in clinical practice. Fine needle aspiration cytology (FNAC) is a reliable preoperative screening test to differentiate between benign and malignant lesions which helps in proper management of patient and avoiding unnecessary surgeries.Aims and Objectives: The present study was to evaluate various lesions of thyroid and classify them according to the Bethedsa system of reporting of thyroid cytopathology (TBSRTC) and to correlate FNAC with histopathology wherever possible.Materials and Methods: This study is a retrospective study of 225 cases of thyroid swelling conducted from May 2016 to April 2017 in the department of pathology, Government Royapettah Hospital, Kilpauk Medical College, Chennai. FNAC results were correlated with histopathological diagnosis wherever surgery was done.Results: This study includes 225 cases. Out of 225 cases of FNAC of thyroid lesions, 213 satisfactory cases were obtained. Maximum cases were benign lesion 233 cases (93.3%), malignant cases were 12 (5.3%) and 12 cases were unsatisfactory (5.3%) with diagnostic accuracy 99%, sensitivity 99% and specificity 100%.Conclusion: FNAC is an effective tool for diagnosing various thyroid lesions as it is safe, cost effective and initial diagnostic modality that avoids unwanted surgeries.